Dictionary of Fantasy Terms - Dayangku Alina Awang Habuan (Universitas Khairun, 2021)
Today fantasy has become a renown genre not only in the literature, but also in the pop-culture such as TVs and movies. Even in the movies, there are considerable number of the fantasy genre, and among those movies, The Lord of The Rings (LOTR) and Harry Potter (HP) are ranked at the top. Moreover, based on Gamble and Yates’ explications, LOTR franchises fall into category (1) because they tell a story of a whole new universe. While HP franchises fall into category (2) and (3) because the stories are about secondary world which can be entered through various portal, and indeed, that’s a ‘world within-a-world’. This means that, both movies are considered as a ‘high fantasy’. Furthermore, this such could be more interesting when the focus is highlighted to the elements, words, or terms that constitute a fantasy genre, for instance, terms which refer to a certain creature or people in the realm of fantasy. These data thus can be compiled into one set of entries, which leads to a project of dictionary-making. In short, the purpose of this project is to conduct a mini scale dictionary contains words in relation to the fantasy genre, especially LOTR and HP universes. Since they are the most popular and categorized as ‘high fantasy’ which contains more reference concerning the fantasy terms.